Market Integration as a Determinant of Household Decision - Making in the Production of Roselle Plant in Mwea Sub - County - Kyalo, Justin; Njoroge, Lawrence (International Journal of Academic Research in Business and Social Sciences, 2015)
This study sought to analyze market integration as determinant of household decision-making in the production of Roselle plant in Mwea Sub-County. This study employed a descriptive survey since this method is designed to obtain pertinent and precise information concerning the status of phenomena and whenever possible to draw valid general conclusions from the facts discovered. The target population was 200 farmers drawn from four areas i.e. Karie, Kangai, Ngariama and Mutithi. The sampling technique used in this study was the stratified type since the population is divided into four strata. Data collected was analyzed qualitatively and quantitatively using SPSS tool and presented in form of frequencies, pie-charts, tables, and graphs. The results indicated that market integration was influencing farmers’ decisions to take up growing Roselle through respondents selling their produce as groups and also the agreement the farmers had with the processing company which enabled them to sell their produce to the company. Some of the recommendations made were the need to carry out further research on how the other parts of the Roselle plant like the roots, leaves, stem and seeds can be used to avoid disposing them yet they could be having potentials just like the calyces
Keywords: Market integration; Farmers; Roselle; Calyces